2010
DOI: 10.1136/gut.2009.187989
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for intractable constipation

Abstract: Objective Traditional surgical procedures for intractable idiopathic constipation are associated with a variable outcome and substantial morbidity. The symptomatic response, physiological effect and effect on quality of life of sacral nerve stimulation (SNS) were evaluated in patients with constipation (slow transit and normal transit with impaired evacuation). Methods In a prospective study at five European sites patients who failed conservative treatment underwent 21 days test stimulation. Patients with >50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
203
5
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(223 citation statements)
references
References 29 publications
3
203
5
12
Order By: Relevance
“…Of the articles included in the analysis, 16 focused on chronic constipation, 11,[24][25][26][32][33][34][35][36][37][38][39][40][41][42] 11 enrolled patients with IBS-C, 27,43-51 with one also including patients with mixed bowel patterns. 48 One study did not differentiate IBS-C from constipation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the articles included in the analysis, 16 focused on chronic constipation, 11,[24][25][26][32][33][34][35][36][37][38][39][40][41][42] 11 enrolled patients with IBS-C, 27,43-51 with one also including patients with mixed bowel patterns. 48 One study did not differentiate IBS-C from constipation.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining seven publications described trials using a cross-over design 32,40 or were unblinded cohort studies. 35,[37][38][39]51 Five trials compared two active agents with each other, 27,33,35,42,52,53 with the other trials using placebos as controls (Table 1). Most trials relied on medical, herbal, or dietary interventions, with only one trial describing the effect of biofeedback 35 and 2 studies reporting the effect of subtotal colectomy 39 or sacral nerve stimulation, 37 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patients with SCT and no defecatory dysfunction commonly experience clinical worsening in response to fiber, and usually respond poorly to routine laxatives (including stimulant laxatives). In this subgroup of patients sacral nerve root neuromodulation (47), as well as subtotal colectomy with ileorectal anastomosis for highly selected cases, may effectively achieve satisfactory results (48,49).…”
Section: How Can the Severity Of Irritable Bowel Syndrome With Constimentioning
confidence: 99%
“…A 2007 Cochrane Database of Systematic Reviews meta-analysis found an increase from 2 to 5 in weekly stools, and improved abdominal pain and distension (47). Most relevant is a European multicenter study in 62 patients: the device was permanently implanted in 73% of patients, with sustained constipation, pain, and distension improvement at 28 months of follow-up.…”
Section: Efficacymentioning
confidence: 99%
“…Its indication has been gradually extended to patients with sphincteric defects (6-10), hence there is an ever increasing number of incontinent patients that are eligible for this procedure, also including stimulators indicated for constipation (11) and pain (12). As with all surgical skills, neuromodulation also displays a learning curve that may be shortened with workshops on stimulators and cadaveric training but cannot be obviated.…”
Section: Introductionmentioning
confidence: 99%